Pacific Collections at the Australian National University Library – Impacts of the Chifley Flood. Issue 2 (3rd April 2019) - Foley, Thomas
Abstract: The Australian National University (ANU) Library is comprised of five specialist branches. ANU Library collections have been developed over the last 50 years by academics and library staff to support world class research and study at ANU. On Sunday 25 February 2018, flooding inundated the ANU Chifley branch of the ANU Library, resulting in damage to collections related to Australian and general History, Philosophy and Religion as well as some relevant microform resources to Pacific research.